Effect of a keto acid-amino acid supplement on the metabolism and renal elimination of branched-chain amino acids in patients with chronic renal insufficiency on a low protein diet - Teplan, V; Schück, O; Horácková, M; Skibová, J; Holecek, M (Wiener klinische Wochenschrift, 2000)
The aim of our study was to evaluate the effect of a low-protein diet supplemented with keto acids-amino acids on renal function and urinary excretion of branched-chain amino acids (BCAA) in patients with chronic renal insufficiency (CRI). In a prospective investigation 28 patients with CRI (16 male, 12 female, aged 28-66 yrs, CCr 18.6 +/- 10.2 ml/min) on a low-protein diet (0.6 g of protein /kg BW/day and energy intake 140 kJ/kg BW/day) for a period of one month were included. Subsequently, this low protein diet was supplemented with keto acids-amino acids at a dose of 0.1 g/kg BW/day orally for a period of 3 months. Examinations performed at baseline and at the end of the follow-up period revealed significant increase in the serum levels of BCAA leucine (p < 0.02), isoleucine (p < 0.03), and valine (p < 0.02) while their renal fractional excretion declined (p < 0.02, p < 0.01 resp.). Keto acid-amino acid administration had no effect on renal function and on the clearance of inulin, para-aminohippuric acid. Endogenous creatinine and urea clearance remained unaltered. A significant correlation between fractional excretion of sodium and leucine (p < 0.05) and a hyperbolic relationship between inulin clearance and fractional excretion of BCAA (p < 0.01) were seen. Moreover, a significant decrease in proteinuria (p < 0.02), plasma urea concentration and renal urea excretion and a rise in albumin level (p < 0.03) were noted. We conclude that in patients with CRI on a low protein diet the supplementation of keto acids-amino acids does not affect renal hemodynamics, but is associated--despite increases in plasma concentrations--with a reduction of renal amino acid and protein excretion suggesting induction of alterations in the tubular transport mechanisms.
Keywords: dospělí; Amino Acids, Branched-Chain; dietní proteiny; Female; esenciální aminokyseliny; chronické selhání ledvin; Adult; ženské pohlaví; Dietary Supplements; Dietary Proteins; lidé; potravní doplňky; následné studie; Kidney Failure, Chronic; prospektivní studie; Follow-Up Studies; Male; Aged; Prospective Studies; Kidney Function Tests; Keto Acids; Amino Acids, Essential; vyšetření funkce ledvin; ketokyseliny; lidé středního věku; senioři; mužské pohlaví; větvené aminokyseliny; Middle Aged; Humans